Analisis Faktor Yang Mempengaruhi Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2015 - 2017 - Rika Mei Hayani Ginting (Jurnal Manajemen Dan Akuntansi Medan, 2019)
The preparation of financial statements by management aims to convey information about the financial condition and size of the company's performance in a certain period. One of the parameters used to measure company performance is information about earnings. Information about earnings is an important element used by users of financial statements both internal and external parties in decision making. Earnings information must reflect the company's actual economic and financial situation, but in reality often management manipulates the financial statements by raising profits to maximize their own satisfaction. Tax planning is related to reporting higher corporate profits. Therefore, company management will use various earnings management techniques to achieve the target. Tax planning and earnings management are related in one another, because they both aim to achieve profit targets by manipulating earnings figures in the financial statements. Various actions taken by the company to show that tax planning is done by manipulating the company's operating activities